(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Arthrosis is one of the degenerative diseases of the joints and often occurs in people with advanced age. This disease causes changes in the tissues of the joints, especially in the bones and cartilage. As a result, it causes pain, movement restrictions and deformities of the joints. For patients suffering from osteoarthritis, the importance of physical education and an active lifestyle is great. Physical activity helps not only to improve the function of the joints, but also to strengthen general health.